Exploring monitoring strategies for population surveillance of HPV vaccine impact using primary HPV screening - Louiza S. Velentzis; David Hawkes; Michael Caruana; Julia ML. Brotherton; Megan A. Smith; Lara Roeske; Khurram A. Karim; Suzanne M. Garland; C. David Wrede; Jeffery Tan; Cosette Wheeler; Philip E. Castle; et al. (Tumour Virus Research, 2023)
Australia's cervical screening program transitioned from cytology to HPV-testing with genotyping for HPV16/18 in Dec’2017. We investigated whether program data could be used to monitor HPV vaccination program impact (commenced in 2007) on HPV16/18 prevalence and compared estimates with pre-vaccination benchmark prevalence. Pre-vaccination samples (2005–2008) (n = 1933; WHINURS), from 25 to 64-year-old women had been previously analysed with Linear Array (LA). Post-vaccination samples (2013-2014) (n = 2989; Compass pilot), from 25 to 64-year-old women, were analysed by cobas 4800 (cobas), and by LA for historical comparability. Age standardised pre-vaccination HPV16/18 prevalence was 4.85% (95%CI:3.81–5.89) by LA; post-vaccination estimates were 1.67% (95%CI:1.21–2.13%) by LA, 1.49% (95%CI:1.05–1.93%) by cobas, and 1.63% (95%CI:1.17–2.08%) for cobas and LA testing of non-16/18 cobas positives (cobas/LA). Age-standardised pre-vaccination oncogenic HPV prevalence was 15.70% (95%CI:13.79–17.60%) by LA; post-vaccination estimates were 9.06% (95%CI:8.02–10.09%) by LA, 8.47% (95%CI:7.47–9.47%) by cobas and cobas/LA. Standardised rate ratios between post-vs. pre-vaccination rates were significantly different for HPV16/18, non-16/18 HPV and oncogenic HPV: 0.34 (95%CI:0.23–0.50), 0.68 (95%CI:0.55–0.84) and 0.58 (95%CI:0.48–0.69), respectively. Additional strategies (LA for all cobas positives; combined cobas and LA results on all samples) had similar results. If a single method is applied consistently, it will provide important data on relative changes in HPV prevalence following vaccination.